Фразеологізми в епістолярії Пантелеймона Куліша - Устенко, Л. (Лексикографічний бюлетень, 2011)
The phraseological units of epistolary by P.Kulish were analyzed in the article. Attention
was concentrated on quantitative and qualitative usage of phraseological units in the
Ukrainian letters by P.Kulish to his contemporaries.Frequency of usage of phraseological units of bookish, biblical, colloquial characters,
their semantic-structural and stylistic features have been studied. Functioning of phraseological
units with additional notional shades and also individual author’s idioms were
demonstrated there.
Illustrative material from epistolary heritage of P.Kulish during 1844 – 1897 has been
presented. The phraseological units and proverbs from bible sources, exactly: comparative
constructions, sayings, aphoristic expressions were fixed. Among selected phraseological
units such ones were considered which receive other contextual meaning than
that meaning which is fixed in phraseological dictionaries.
Great number of proverbs in the letters by P.Kulish is a fact that has been stressed upon.